The Constitution as the Embodiment of Political Philosophical Values - Yunus, Nur Rohim (BULETIN ADALAH, 2023)
This essay discusses how the constitution manifests the values of political philosophy that underlie a country. The constitution functions as the highest legal document and reflects the ideals of politics, justice, and ideal governance. However, in its implementation, the country often faces a dilemma between the perfect norms of the constitution and the existing social, political, and economic realities. This essay examines various foundations—philosophical, sociological, and legal—that strengthen the constitution as a reflection of the values of political philosophy. In addition, it also discusses the debate on the flexibility of the constitution and the challenges in balancing local and universal values. Finally, this essay offers ideal recommendations so that the constitution remains relevant, can accommodate the dynamics of society, and functions as the central pillar of a democratic state.